Modelo de análisis financiero de sistemas de producción de leche y compañías comparables del sector agropecuario - Molina-Aguilar, Gabriela; Murillo-Quesada, Ronald (Instituto Tecnológico de Costa Rica, 2016)
Today, Costa Rica faces several challenges in the dairy sector such as, adaptation to climate change and the market competition due to the free trade agreement with a number of countries and commercial sectors (TLC). In this sense, the free trade agreement with the USA (CAFTA) is the most significant one, since it was the closest one to be implemented, and its tariff reduction. Because of that, Costa Rican dairy producers need to be more efficient and find new alternatives and strategies to keep up with the international market. In order for this to occur, it is fundamental to have all the company financial information and analyze it, to set better strategies according to their own conditions. That been said, we will study and analyze the behavior or evolution of the three different dairy production systems in Costa Rica: grazing, semi confinement and confinement during a three-year-period (2013, 2014 y 2015) to understand the cost structure, operational and net profit and recommend key financial improvements that may result into company value added increase. x The financial analysis described above, will be compared against the USA agricultural sector to determine how competitive the national market is, and help set forth an objective strategy Once finished, there will be an Excel spreadsheet model for the analysis to be repeated by dairy producers as a tool to improve decision-making.
Proyecto de Graduación (Maestría en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2016.
Keywords: Lecherías; Eficiencia; Finanzas; Estrategia; Modelo de negocios; Toma de decisiones